Impact of Terrorism and the Role of Media in Islamophobia Propaganda (Systematic Literature Review) - Anadza Iron Albaroza; Rizky Bagastian; Anita Anita; Iradhad Taqwa Sihidi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The terrorist movement has often been heard of, both in Indonesia and from other parts of the country. Several studies discuss whether terrorism is included in the impact of globalization where the movement quickly spreads with globalization and becomes a form of transnational movement that eventually enters other countries and develops rapidly and promptly distributes ideas to existing ones. First, identify the article. The article was taken from the publications of various authors using a database from Scopus. The next step is to enter the keyword "ISLAMIC TERRORISM" in the publish column and be given a discussion of the year of publication only for the last few years, namely from 2018 to 2021. The media plays an essential role in acts of terrorism, both in spreading networks to acts of terror. Cyber terrorism is ubiquitous, it is more flexible than traditional terrorism, and cyber-attacks mostly occur in the country of origin. Thereby discussing the complex features of cyberterror networks and identifying some of the geostrategic implications of cyber strategy. The public should be able to sort out the information they get to the stage of proving who the terrorist network is involved in the terror act. It is hoped that this will be able to consume information wisely and not be carried away by propaganda that can endanger oneself, family, and society.